2013
DOI: 10.1534/genetics.113.156570
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Targeted Mutagenesis in Mice Using TALENs

Abstract: Targeted mouse mutants are instrumental for the analysis of gene function in health and disease. We recently provided proof-of-principle for the fast-track mutagenesis of the mouse genome, using transcription activator-like effector nucleases (TALENs) in one-cell embryos. Here we report a routine procedure for the efficient production of disease-related knockin and knockout mutants, using improved TALEN mRNAs that include a plasmid-coded poly(A) tail (TALEN-95A), circumventing the problematic in vitro polyaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 38 publications
(55 reference statements)
1
39
0
2
Order By: Relevance
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 90%
“…11). While this manuscript was in preparation such findings have been extended to the mouse using a similar strategy for homologous recombination in mice that utilizes either short ssDNA donor templates or donor vectors to correct a single base mutation 12,13 . This work demonstrated that a donor vector with long homology regions, similar to the one used for this study, can be used for homology-directed repair in oocytes to exchange single base mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab3 (Wada et al, 1997) 1 (Figueiredo et al, 2008) 2 Rab27 (Mahoney et al, 2006) 4 (Figueiredo et al, 2008) 2 (Yoshimura et al, 2010) 1 Rab3, Kif1a, Kif1b, DR4, DR5, TNFR1, JNK3, LRDD, IA-2 (Marat et al, 2011) Rabconnectin-3 (Kawabe et al, 2003) Madd-null mice (Tanaka et al, 2001) C. elegans aex-3 mutant (Iwasaki et al, 1997) DENN-related FLCN (201163) folliculin Rab35 (Nookala et al, 2012) 1 GAP for RagC/D GTPase (Tsun et al, 2013) Birt-Hogg-Dubé syndrome Flcn-, Fnip1-, Fnip2-null mice (Schmidt and Linehan, 2015) FNIP1 ( C9ORF72 (427370) DENNL72 ND Rab1, Rab5, Rab7, Rab11, ubiquilin-1/2, hnRNPA1, hnRNPA2/B1, actin (Farg, et al, 2014) C9orf72-null mice (Panda et al, 2013;Koppers et al, 2015) Fronto-temporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) (Lattante et al, 2015) SMCR8 ( …”
Section: Denn and Denn-related Proteinsmentioning
confidence: 99%
“…Like ZFN, Tale repeats are linked together in order to recognize specific DNA sequences. TALEN has been rapidly and widely used to perform precise genome editing in a wide range of cell types and organisms, including rats, mice (Panda et al, 2013), human and livestock (Moghaddassi et al, 2014).…”
Section: Transcription Activator-like Effector Nucleases (Talen)mentioning
confidence: 99%